2012
DOI: 10.1074/jbc.m111.338350
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Androgen Receptor by PIM-1 Kinases via Phosphorylation-dependent Recruitment of Distinct Ubiquitin E3 Ligases

Abstract: Background:The androgen receptor (AR) plays a critical role in prostate cancer development and progression. Results: Oncogenic PIM-1 kinases directly interact with AR and induce AR phosphorylation at multiple residues. Conclusion: PIM-1 kinases differentially modulate AR activity via phosphorylation-dependent recruitment of distinct ubiquitin E3 ligases. Significance: Our findings provide new insights into mechanisms by which AR activity may be regulated in prostate cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 74 publications
0
62
0
Order By: Relevance
“…AKT has been reported to phosphorylate Ser213 in the AR N-terminus and thereby enhance its ubiquitylation and degradation in human PCa cells (3436), but this effect may be cell line and passage number dependent (17, 3739). Moreover, further studies indicate that PIM1 is the major mediator of AR Ser213 phosphorylation (40, 41), while another study found that PI3K enhanced AR stability and activity by AKT independent mechanisms (15). Studies in mice with prostate specific PTEN loss are also somewhat conflicting as one study found that PI3K pathway activation suppressed AR expression (42) while a second study found decreased AR transcriptional activity but not decreased AR expression (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKT has been reported to phosphorylate Ser213 in the AR N-terminus and thereby enhance its ubiquitylation and degradation in human PCa cells (3436), but this effect may be cell line and passage number dependent (17, 3739). Moreover, further studies indicate that PIM1 is the major mediator of AR Ser213 phosphorylation (40, 41), while another study found that PI3K enhanced AR stability and activity by AKT independent mechanisms (15). Studies in mice with prostate specific PTEN loss are also somewhat conflicting as one study found that PI3K pathway activation suppressed AR expression (42) while a second study found decreased AR transcriptional activity but not decreased AR expression (43).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in human PCa cells have found that AKT can phosphorylate AR at a site in its N-terminal domain (Ser213) and thereby decrease AR transcriptional activity or enhance its ubiquitylation and degradation by MDM2 (3436), while other studies show that AKT mediated phosphorylation of AR can increase AR protein and activity (17, 3739). Further studies indicate that PIM1, rather than AKT, is the major mediator of AR Ser213 phosphorylation (40, 41), and that PI3K may enhance AR stability and activity by AKT independent mechanisms (15). Finally, one study in genetically engineered mice with prostate specific PTEN loss indicates that PI3K pathway activation suppresses AR expression (42), while another study found that AR transcriptional activity, but not AR expression, was decreased (43).…”
Section: Introductionmentioning
confidence: 99%
“…At least two kinases, Akt and PIM-1, are known to phosphorylate S213 with different functional consequences (Wen et al 2000; Lin et al 2001; Lin et al 2003; Taneja et al 2005; Palazzolo et al 2007; Ha et al 2012; Kasina & Macoska 2012; Linn et al 2012; Varisli et al 2012). Moreover, Akt-dependent AR S213 phosphorylation is regulated by several signaling pathways (Wen et al 2000; Kasina & Macoska 2012; Varisli et al 2012).…”
Section: S213 S791 and T850 Phosphorylationmentioning
confidence: 99%
“…AR S213 was also shown to be a target for PIM-1 kinase (Linn et al 2012). PIM-1 has two isoforms, 44 kDa PIM-1L and 33 kDa PIM-1S (Saris et al 1991), both of which can directly interact with the AR and phosphorylate it at different residues, namely S213 and T850.…”
Section: S213 S791 and T850 Phosphorylationmentioning
confidence: 99%
“…PIM kinases might influence self-renewal and reprogramming through direct phosphorylation of BCRP/ABCG2, a putative stem cell marker, which may be involved in multiple drug resistance57. PIM kinases might regulate androgen receptor (AR) turnover by phosphorylation58. Therefore, PIM1-dependent phosphorylation of AR regulates gene transcription, especially STAT3, which is prevalent in aggressive prostate cancer2759.…”
Section: Discussionmentioning
confidence: 99%